ANALISIS PENGARUH INOVASI PRODUK DAN GAYA HIDUP BRAND MINDED TERHADAP PERILAKU PEMBELIAN KONSUMEN - Rohimah, afifatur; Tjahjono, Endro; Pujianto, Agung (Jurnal Dinamika Administrasi Bisnis, 2015)
Advances in technologyin the eratecnologyspeed, the speed ofinformationandthe ease ofcommunicating viathe gadgetbecomesindispensable. Inthis casethe peopleare alwaysin need ofproductinnovation, accompanied by alifestylebrandminded, resulting inthe emergence ofconsumerpurchasebehavior. This research wasquantitativewithmultiple linearregressionanalysismethod. The goal istodetermine the influence ofproduct innovationandlifestylebrandmindedtowardsthe purchaseof consumer behavior. Based onthe research results, it is known that theinnovationof productsandlifestylebrandmindedvery strong influence onconsumerbuyingbehavior. Whilelifestylebrandmindeddominantinfluenceonconsumer behaviorinpurchasingofproduct innovation. Looking atthe results ofthe study, the researcherssuggestthat peoplekeep abreast ofproduct innovation andmanufacturerswithout having tohave it, andreducinglifestylebrandmindedso as to reducethe level ofconsumer behaviorthat resulted inthe purchase ofstate of Indonesiabecamethemostconsumptivestate. Keywords: productinnovation, brandmindedlifestyle, consumer behavior.